2011
DOI: 10.5194/bgd-8-6637-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of phytoplankton community structure in the South China Sea in response to the East Asian aerosol input

Abstract: Recent studies have regarded atmospheric deposition as an increasingly important source of nutrients to the ocean. The South China Sea (SCS), where aerosol loading is among the highest in the world, however, is poorly studied particularly on the in situ changes of phytoplankton community structures in response to atmospheric deposition. By conducting a series of microcosm bioassays at different hydrographical locations and simulating different aerosol event scales, we observed both positive and negative respon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 83 publications
(17 reference statements)
5
24
0
Order By: Relevance
“…For example, fourfold increases of Chl a concentration during episodic dust events have been reported in the northern SCS (Wang et al, ). The two mechanisms of nutrient supplementation by aerosol deposition are presumed to be direct nutrient inputs from the deposited aerosols (Guo et al, ) and upper ocean N 2 fixation stimulated by eolian Fe input (Gaye et al, ; Kao et al, ). In our sampled sinking particles (Table ), the relatively high particulate nitrogen (PN) flux, the high percentage of PN in the biogenic matter, and the moderate Fe 2 O 3 and Al 2 O 3 proportions (Liu et al, ) indicate that the primary factor serving to enhance surface Chl a concentrations seems to have been direct nutrient inputs rather than Fe stimulation of diazotrophic activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fourfold increases of Chl a concentration during episodic dust events have been reported in the northern SCS (Wang et al, ). The two mechanisms of nutrient supplementation by aerosol deposition are presumed to be direct nutrient inputs from the deposited aerosols (Guo et al, ) and upper ocean N 2 fixation stimulated by eolian Fe input (Gaye et al, ; Kao et al, ). In our sampled sinking particles (Table ), the relatively high particulate nitrogen (PN) flux, the high percentage of PN in the biogenic matter, and the moderate Fe 2 O 3 and Al 2 O 3 proportions (Liu et al, ) indicate that the primary factor serving to enhance surface Chl a concentrations seems to have been direct nutrient inputs rather than Fe stimulation of diazotrophic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The cubitainers were tied on a fish raft and soaked in natural seawater. A neutral density screen was applied to attenuate the sunlight intensity by 40%, approximately the light condition at the surface layer [ Guo et al , ]. All apparatuses used in the experiments were prewashed with 0.2 M ultrapure HCl and then rinsed with MilliQ water.…”
Section: Methodsmentioning
confidence: 99%
“…Atmospheric deposition plays an important role in supplying nutrients and trace elements to marine ecosystems [ Duce et al , ; Zhang et al , ]. These allogenic substances may affect primary productivity [ Bishop et al , ], phytoplankton community structure [ Guo et al , ], and associated sea‐air emissions of biogenic reactive gases containing sulfur [ Andreae , ], nitrogen, and halogen [ Garland et al , ; Prados‐Roman et al , ] and therefore can influence global biogeochemical cycling, atmospheric chemistry, and climate change [ Neuer et al , ]. It was found that mineral dust could increase primary productivity and nitrogen consumption in the laboratory experiment [ Herut et al , ] and the North Atlantic [ Moore et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…This occurs because populations can be limited by different nutrients depending on cellular quotas and physiological requirements. Bottle incubation experiments have been used to identify differences in nutrient (co)limitation between communities in coastal versus offshore waters 70 , 76 , along open ocean transects 77 , 78 , over different seasons 79 , and among sites with varying amounts of anthropogenic influence 80 . For example, aerosol-derived Co, Mn, and Ni supported growth of oceanic (but not coastal) Synechococcus in the Sargasso Sea.…”
Section: Introductionmentioning
confidence: 99%